Exploring the Transnational Neighbourhood Perspectives on Community-Building, Identity and Belonging - Ehrig, Stephan; Jung, Britta Christina; Schaffer, Gad (Leuven University Press, 2022)
Practices of community-building in a globalised context Urban neighbourhoods have come to occupy the public imagination as a litmus test of migration, with some areas hailed as multicultural success stories while others are framed as ghettos. In an attempt to break down this dichotomy, Exploring the Transnational Neighbourhood filters these debates through the lenses of geography, anthropology, and literary and cultural studies. By establishing the interdisciplinary concept of the 'transnational neighbourhood', it presents these localities - whether Clichy-sous-Bois, Belfast, El Segundo Barrio or Williamsburg - as densely packed contact zones where disparate cultures meet in often highly asymmetrical relations, producing a constantly shifting local and cultural knowledge about identity, belonging, and familiarity. Exploring the Transnational Neighbourhood offers a pivotal response to one of the key questions of our time: How do people create a sense of community within an exceedingly globalised context? By focusing on the neighbourhood as a central space of transcultural everyday experience within three different levels of discourse (i.e., the virtual, the physical local, and the transnational-global), the multidisciplinary contributions explore bottom-up practices of community-building alongside cultural, social, economic, and historical barriers. Contributors: Christina Horvath (University of Bath), Maria Roca Lizarazu (NUI Galway), Emilio Maceda Rodriguez (Universidad Autónoma de Tlaxcala), Naomi Wells (IMLR, University of London), Anne Fuchs (University College Dublin), Gad Schaffer (Tel-Hai Academic College), Daniela Bohórquez Sheinin (University of Michigan), Anna Marta Marini (Universidad de Alcalá), Godela Weiss-Sussex (IMLR, University of London), Britta C. Jung (Maynooth University), Emma Crowley (University of Bristol), Mary Mazzilli (University of Essex) Ebook available in Open Access. This publication is GPRC-labeled (Guaranteed Peer-Reviewed Content).